Obstetric outcomes in patients with primary thrombotic and obstetric antiphospholipid syndrome and its relation to the antiphospholipid antibody profile. (June 2019) - Högdén, A; Antovic, A; Berg, E; Bremme, K; Chaireti, R
Introduction : Previous studies suggested different obstetric outcomes between patients with thrombotic or obstetric antiphospholipid syndrome, but the data are inconclusive.Aims : To investigate obstetric outcomes and their relation to the antiphospholipid antibody profile in primary thrombotic or obstetric antiphospholipid syndrome patients and compare those to a control population.Materials and methods : A retrospective single-centre study on a cohort of 30 pregnant women with primary antiphospholipid syndrome treated at Karolinska University Hospital Solna, Sweden between 2000 and 2016. The pregnancy outcomes were compared to the outcomes of all pregnancies in Stockholm County during the same period.Results : Preeclampsia ( p < 0.001), low birth weight at delivery ( p = 0.001), Apgar < 7 at 5 minutes ( p < 0.001) and small infants ( p < 0.001) were more common in antiphospholipid syndrome patients compared to controls. Obstetric antiphospholipid syndrome patients had a higher incidence of small infants ( p = 0.023), lower birth weight ( p = 0.013) and infants born with complications ( p= 0.004) compared to thrombotic antiphospholipid syndrome. Mothers with triple antibody positivity had a higher incidence of preeclampsia ( p = 0.03), preterm delivery ( p = 0.011), small infants ( p= 0.002) and infants born with complications ( p = 0.012).Conclusions : Patients with primary antiphospholipid syndrome, especially those with obstetric antiphospholipid syndrome and triple antibody positivity, are at higher risk for adverse pregnancy outcomes, even under antithrombotic treatment. More frequent antenatal controls in high-risk patients can further improve outcomes.